"Just the Type with whom I Like to Work": Two Correspondence Field Experiments in an Online Mental Health Care Market. (November 2019) - Kugelmass, Heather
Two field experiments investigated discrimination in an online mental health care market. The subjects were 908 mental health care providers (MHPs) who advertise for clients on a website through which help-seekers email providers. Both studies measured MHPs' receptiveness to an ostensibly black or white help-seeker requesting an appointment. In the first study, no racial or gender disparities were observed. However, help-seekers in the second study, who signaled lower education than those in the first, were confronted with significantly lower accessibility overall. Moreover, black help-seekers with low education and high social need (i.e., a caseworker) received significantly fewer positive responses than any other group. Although the two studies are not directly comparable, their results suggest a hierarchy of accessibility: MHPs prefer more educated help-seekers over less educated ones and among those less educated prefer black help-seekers with a caseworker the least. These disparities persist after controlling for MHPs' sociodemographic and financial characteristics.